Contextualization of BTQ Learning in Improving Students' Interest in Learning the Qur’an at Elementary School - Ariandi, Rian; Pahrurraji, Pahrurraji; Rena, Syahidah (ARZUSIN, 2025)
This research aims to analyze the Reading and Writing the Qur'an / Baca dan Tulis Al Qur’an (BTQ) learning model at SD Islam Al Amanah Setu Tangerang Selatan, reveal the implications of the contextualization of BTQ learning, and reveal future developments. The researchers used a qualitative approach with the type of field research. The data and sources in this research were primary and secondary data, while the researchers used data collection techniques through observation, interviews, and documentation. The research results indicate that the contextualization of BTQ learning at SD Islam Al Amanah has three aspects, namely planning, implementation, and evaluation. The implications of the contextualization of BTQ learning in this school are that teachers can remember and deepen the knowledge of the Qur'an, reduce students' difficulties in learning the Qur'an, students are more disciplined and hardworking, patient, independent, honest, have a better attitude, students' grades are according to target, achieve in the field of the Qur'an, and this BTQ learning can be an attraction for schools. The plan for developing BTQ learning at this school is special training for BTQ teachers, increasing BTQ teaching hours, collaboration between parents/guardians and teachers, creating BTQ certificates, and eliminating SPP and BTQ as a requirement for obtaining a diploma.